Playing language games: higher education quality dynamics in Dutch national policies since 1985. Issue 3 (3rd July 2018) - Weenink, Kasja; Aarts, Noelle; Jacobs, Sandra
ABSTRACT: Higher education quality is a vague, ambiguous, multiple, and essentially contested concept. Quality's contested character involves endless disputes about its proper use which makes it problematic to handle in governmental policies. Wittgenstein's notion of language games is used to understand how, through time, higher education quality is enacted in Dutch governmental policy texts, and how its uses are related to each other. The analysis depicts various quality games interacting with different policy contexts, which show multiple enactments of quality as a unified concept alongside more differentiated uses. In the policy games, quality is not the focal notion. The games center around the steering relationship with the institutions, which are placed 'at distance'. Through time, the games respond to increasing societal complexity and competition, and foster further flexibilization of institutional policies regarding quality and accessibility. In this management discourse with the institutions, quality is not used contrastively. It is concluded that quality's vague and contradictory enactments and valuations are not problematic in the institutional steering relationship. Recent policy texts however relate quality's 'proper use' to activities that enhance the student's learning process. This draws attention to paradoxes for a distancing government in its role as a universal actor with societal responsibilities.